Guidelines for Implementing Learning Recession Recovery Measures of the Secretariat of the Education Council in Educational Opportunity Expansion School in Mueang District, Nakhon Nayok Province - Srinakornchaijaroen, Nutsinee; Viseshsiri, Pongsin (CRMA Journal of Humanities and Social Sciences, 2024)
The objectives of this research were to: 1) Study current operational conditions; and 2) Study operational guidelines for implementing learning recession recovery measures according to the Secretariat of the Education Council in Educational Opportunity Expansion Schools in Mueang District, Nakhon Nayok Province. The sample population was 103 government teachers. Research tools were questionnaires and semi-structured interviews. The statistics used were mean, standard deviation, and content analysis. The results showed that the overall operating conditions were at a high level. When considering each measure, the most effective action was designing a new learning management process that responds to the changing context and needs of the learners, followed by creating a positive attitude toward learning and good physical and mental health of learners. The research recommends three measures that should be developed as priorities, namely: 1) Shoring up morale by addressing teachers’ concerns regarding the performance of their duties in high-risk areas, including by providing welfare and creating good understanding; 2) Developing a digital media library for the open learning approach and linking educational information by providing appropriate budgetary and equipment support, enhancing teachers’ knowledge in digital media production, and allowing all to access this library; and 3) Empowering the development of teachers and educational administrators through appropriate policies and allocating budgets for upgrading learning through technology.